2020
DOI: 10.1080/0886022x.2020.1847723
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and renal function in the Italian kidney transplant population

Abstract: Background: The well-documented benefits of physical activity (PA) are still poorly characterized in long-term kidney transplant outcome. This study analyzed the impact over a 10-year follow-up of PA on graft function in Italian kidney transplant recipients (KTRs). Methods: Since 2002, the Italian Transplant-Information-System collected donor and recipient baseline and transplant-related parameters in KTRs. In 2015, 'penchant for PA' (PA ! 30-min, 5 times/week) was added. Stable patients aged !18 years at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…The lowest inclination to physical activity was observed in overweight and obese subjects, as well as in patients with longer dialysis vintage and older age at transplant. Noticeably, the propensity score showed that graft function was better preserved among active KT recipients [ 19 ].…”
Section: Physical Activity Before and After Kidney Transplantationmentioning
confidence: 99%
“…The lowest inclination to physical activity was observed in overweight and obese subjects, as well as in patients with longer dialysis vintage and older age at transplant. Noticeably, the propensity score showed that graft function was better preserved among active KT recipients [ 19 ].…”
Section: Physical Activity Before and After Kidney Transplantationmentioning
confidence: 99%
“…Previous studies found patients on the transplant waitlist did not consider exercise to be a factor in the health of their kidneys [19]. Recent work has shown an association between exercise and slower post-transplant eGFR decline [20]. Nearly all (98%) of our surveyed patients reported exercise was important to the health of their kidneys and 90% believed maintaining a healthy weight was important to the health of their kidneys.…”
Section: Discussionmentioning
confidence: 71%
“…Many solid organ transplant recipients lead a sedentary, physically inactive life [7][8][9][10][11]. Sedentary behaviour refers to "any waking behaviour characterized by an energy expenditure of ≤1.5 metabolic equivalents, while in a sitting, reclining, or lying posture" [12].…”
Section: Physical Inactivity After Organ Transplantation: Prevalence ...mentioning
confidence: 99%
“…Both in the general and the transplant population, physical activity and physical fitness are established risk factors for cardiovascular disease [10,28,[34][35][36][37][38], which currently represents one of the leading causes of death following transplantation [30,33,39,40]. Observational studies in kidney transplant recipients have suggested that physical activity may contribute to preservation of graft function [9,41], although intervention studies still need to confirm such findings. Lastly, in the general population, regular engagement in physical activity enhances immunosurveillance against pathogens [42] and adverse outcome following SARS-CoV-2 infection [43].…”
Section: Physical Inactivity After Organ Transplantation: Prevalence ...mentioning
confidence: 99%